Jaminan Goverment Guarantee Dalam Kredit Sindikasi (Sebagai Alternatif Pembiayaan Infrastruktur Jalan Tol) - Imanunggal Adhi Saputro; Anas Lutfi; Sadino Sadino (Jurnal Ilmu Hukum, Humaniora dan Politik, 2023)
The development of an area that has an impact on the community's economy and the fulfillment of the community's basic needs requires the development of road infrastructure that supports the distribution process to run quickly and efficiently. This development is to fulfill the mobility of the community so that they become mutually connected with other regions in order to create acceleration of regional development. The state in meeting the infrastructure needs for the development of the region is expected to be able to improve the surrounding economy and other areas that are connected to the construction of the road infrastructure. Based on the provisions of Law Number 38 of 2004 concerning Roads in Article 43 it states that toll roads are built to facilitate traffic in developing areas, to increase mobility and distribution of basic needs and industrial commodities. Toll roads are one of the infrastructures that are considered effective in meeting the mobility needs of the community. The construction of the toll road is a development project that requires a large amount of money. The government provides funding concessions for Business Entities appointed to carry out the construction of toll roads. One of the financing instruments that can be used by Business Entities in meeting the funding needs for Toll Road development is syndicated bank loans. Syndicated bank loans can be used with a guarantee, one of which is a Government Guarantee or Government Guarantee. The aim of this research is to know and understand the legal standing of government guarantees in syndicated bank loans. The legal theory used is Normative Law Theory to find the truth based on the applicable positive law. This legal research method is empirical juridical based on the school of sociological jurisprudence based on normative law by observing laws and regulations. The results of the study found that syndicated loans are different from single loans in circulation in general. Syndicated credit begins with the stages of offering credit to syndicated participants (participants), giving mandates, memorandum information, meeting prospective debtors to obtain syndicated credit approval, signing the credit agreement and ending with publication. Guarantees on syndicated loans are preferred creditors who have the right to pay off credit first.